2020
DOI: 10.1038/s41598-020-68696-7
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis on predicting the impact of high-risk SNPs in human secretary phospholipase A2 receptor (PLA2R1)

Abstract: PLA2R1 is a transmembrane glycoprotein that acts as an endogenous ligand which stimulates the processes including cell proliferation and cell migration. The SNPs in PLA2R1 is associated with idiopathic membranous nephropathy which is an autoimmune kidney disorder. The present study aimed to explore the structure-function analysis of high risk SNPs in PLA2R1 by using 12 different computational tools. First the functional annotation of SNPs were carried out by sequence based tools which were further subjected to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“… 58 Growing evidence suggests that sQTL SNPs occurring at 5' UTR are involved in transcriptional activation, as the H3K4me3 marks are enriched in the 5' end of gene bodies, which normally includes the 5′ UTRs. 59 In addition, the sGenes contained in the turquoise module were also enriched in brain-related disorders ( Figure 4 E), especially in multiple neurodegenerative diseases (including Alzheimer and Parkinson), which is consistent with the results of enrichment analyses of sQTL SNPs among disease-associated loci.…”
Section: Discussionsupporting
confidence: 82%
“… 58 Growing evidence suggests that sQTL SNPs occurring at 5' UTR are involved in transcriptional activation, as the H3K4me3 marks are enriched in the 5' end of gene bodies, which normally includes the 5′ UTRs. 59 In addition, the sGenes contained in the turquoise module were also enriched in brain-related disorders ( Figure 4 E), especially in multiple neurodegenerative diseases (including Alzheimer and Parkinson), which is consistent with the results of enrichment analyses of sQTL SNPs among disease-associated loci.…”
Section: Discussionsupporting
confidence: 82%
“…In this study, the missense variations were selected in order to investigate their damaging effects and how they influence the phenotypic characteristics of the respective encoded protein. These missense variations are responsible for various complex diseases by affecting the protein’s functional activities and structural stability or folding ( Khalid & Almaghrabi, 2020 ; Shahid et al, 2022 ). A list of all 610 missense variants is presented in Table S1 .…”
Section: Resultsmentioning
confidence: 99%
“…To enhance prediction accuracy, we integrated tools from diverse categories, including homology-based, sequenced-based, consensus-based, and structure-based approaches. This strategy aims to increase confidence in the identification of potentially detrimental missense SNPs by mitigating biases in the results 50 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, stability analysis indicated that five SNPs (R144C, I148N, S172W, A297D, and L312Q) among the 17 pathogenic SNPs could lead to a decrease in OX1R stability, based on the results of all seven prediction tools. Protein stability is a critical characteristic that affects its structure, function, evolution, and biological activity, as well as its normal pathways 50 . Any modification of protein stability may contribute to aberrant accumulation, misfolding, or protein degradation 51 .…”
Section: Discussionmentioning
confidence: 99%